1990
DOI: 10.1111/j.1365-2125.1990.tb03794.x
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation pathways in liver disease.

Abstract: 1 The activities of microsomal glucuronyltransferase and thiomethyltransferase, and those of cytosolic sulphotransferase, acetyltransferase, glutathione transferase and thiomethyltransferase were measured in abnormal (cirrhosis and chronic hepatitis) and normal livers. 2 Glucuronyltransferase and sulphotransferase were investigated with 2-naphthol and ethinyloestradiol as substrates. p-Aminobenzoic acid, benzo(a)pyrene-4,5-epoxide and 2-mercaptoethanol were the substrates of acetyltransferase, glutathione tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 22 publications
(23 reference statements)
2
10
0
Order By: Relevance
“…A fraction of a delafloxacin dose is conjugated by the liver into glucuronidated metabolites for excretion by the kidneys, and this process is facilitated through the liver . However, unlike hepatic metabolism through the cytochrome P450 system, phase 2 conjugation by the liver is rarely impacted by hepatic disease until there is severe damage . Therefore, one might predict that hepatic disease would not be a major factor in the disposition of delafloxacin and its glucuronide metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A fraction of a delafloxacin dose is conjugated by the liver into glucuronidated metabolites for excretion by the kidneys, and this process is facilitated through the liver . However, unlike hepatic metabolism through the cytochrome P450 system, phase 2 conjugation by the liver is rarely impacted by hepatic disease until there is severe damage . Therefore, one might predict that hepatic disease would not be a major factor in the disposition of delafloxacin and its glucuronide metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…13 However, unlike hepatic metabolism through the cytochrome P450 system, phase 2 conjugation by the liver is rarely impacted by hepatic disease until there is severe damage. 14,15 Therefore, one might predict that hepatic disease would not be a major factor in the disposition of delafloxacin and its glucuronide metabolites. However, because a large percentage of delafloxacin is cleared by the kidneys (ß65%), whether as intact molecule or the conjugated metabolites, we also could have a confounding variable in subjects with varying degrees of renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Many drugs induce a significant release of more unconjugated fraction with chronic liver disease; such drugs may be metabolized more rapidly in patients with cirrhosis (Delcò et al, 2005). However, Pacifici et al (1990) demonstrated that liver disease reduces the activities of sulfotransferase, acetyltransferase, glutathionetransferase, and thiomethyltransferase. The plasma AUC of unconjugated silibinin was significantly reduced in the presence of liver cirrhosis, which might be due to a decrease in the enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…[Figure 3 near here] [Table 4 near here] Among Phase 2 reactions, sulfation reactions are more notably affected by liver injury, when compared to glucuronidation [Elbekai et al , 2004]. Historically glucuronidation has been viewed as being spared by the effects of hepatic impairment [Pacifici et al , 1990, Choo et al , 1999, Verbeeck, 2008], but there has been more evidence that suggests that effects on glucuronidation maybe significant in severe liver impairment and for drugs undergoing ester, as opposed to ether, glucoronidation (e.g., zidovudine) [Brouwer et al , 1992]. …”
Section: Impact On Pharmacokinetic Processesmentioning
confidence: 99%